A Study on Product Life Cycle Management – ICICI Bank (International Journal of Food and Nutritional Sciences, 2021)
Product life cycle management is the succession of strategies used by management and as a product goes through its product life cycle. The conditions in which a product is sold changes over time and must be managed as it moves through its succession of stages.It is claimed that every product has a life period, it is launched, it grows, and at some point, may die. A fair comment is that - at least in the short term - not all products or services die. Jeans may die, but clothes probably will not. Legal services or medical services may die, but depending on the social and political climate, probably will not. Even though its validity is questionable, it can offer a useful 'model' for managers to keep at the back of their mind. Indeed, if their products are in the introductory or growth phases, or in that of decline, it perhaps should be at the front of their mind; for the predominant features of these phases may be those revolving around such life and death. Between these two extremes, it is salutary for them to have that vision of mortality in front of them.